Evaluation of the antifungal activity of marine actinomycetes isolates against the phytopathogenic fungi Colletotrichum siamense KA: A preliminary study for new antifungal compound discovery - Qonita Gina Fadhilah; Iman Santoso; Andi Eko Maryanto; Sarini Abdullah; Yasman Yasman (Pensoft Publishers, 2021)
Marine actinomycetes are being explored to discover potential actinomycetes that produce antifungal compounds. In a previous study, marine actinomycetes isolates from the mangrove ecosystem were found to inhibit growth of the phytopathogenic fungi Colletotrichum siamense KA. In this study, the three of these isolates with the highest antagonistic activity-SM11, SM14, and SM15-were evaluated for their antifungal activity using antibiosis assay. The fermentation was performed in SCB:PDB medium (1:1) for 6, 9, and 12 days. The results showed that SM14 was the strongest potential isolate; it inhibited the growth of C. siamense KA on average up to 64.90% for 12 days on PDA filtrate medium. Molecular identification showed SM14 was closely related to Streptomyces sanyensis, but had differences in morphological and biochemical characteristics compared to SM11 or SM15. This indicated that the three isolates were different strains and may challenge further research on identifying and analyzing their antifungal compounds.